Synthesis of Research Identifying Components of a Native Model for Electronic Evaluation Systems in the Islamic Azad University of Iran - Rezaii, Shahla; Malekian, Faramarz; Mohmmadi, Sahar; Ghasemi, Alireza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: With the entry of the digital generation (a generation born and raised in the presence of technology) into universities, which demands a different method and style of learning from the past generation, the higher education system is compelled to move towards creating educational infrastructures that meet the needs of this generation. The current research aims to identify the components of a native model for electronic evaluation systems based on the capabilities and facilities available in our country's higher education system, specifically at the Islamic Azad University of Iran.Methodology: The research approach is qualitative, utilizing a research synthesis strategy. The research population includes all printed and digital documents in our country's information resources, of which 16 documents were selected based on defined criteria and by purposive sampling until data saturation was reached.Findings: The analysis of the collected data was conducted using thematic analysis, resulting in the extraction of 10 categories and 59 components for creating a native electronic evaluation system that can be used as a guide in educational settings.Conclusion: Based on this research, it is possible to evaluate electronic learning courses in the evaluation section.